Framework Administered Account for Selected Fund Activities : The Socialist People's Libyan Arab Jamahiriya Subaccount for Selected Fund Activities. (Policy Papers; Policy Paper ;, 2009)
The Fund, represented by the Managing Director, has reached understandings with Libya acting through the Central Bank of Libya ('Libya'), to finance capacity building (technical assistance and training) and related activities. On the basis of these understandings, the Managing Director has established the essential terms and conditions of the Subaccount, with which The Socialist People's Libyan Arab Jamahiriya concurs, with respect to the nature, design, and implementation of the activities to be financed and the method by which the costs of the activities will be financed from the Subaccount.